N2o emissions from a cultivated Mollisol : optimal time of day for sampling and the role of soil temperature - Cosentino, Vanina Rosa Noemí (2012)
Fil: Cosentino, Vanina Rosa Noemí. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.